Analisis Pengembangan Kemampuan Adaptasi Lingkungan Usaha Kecil Menengah (UKM) Menggunakan Keunggulan Kompetitif Melalui Kinerja Pemasaran - Nadia Dwi Irmadiani (Universitas 17 Agustus 1945, 2024)
Environmental adaptability is the ability, flexibility in dealing with changes and challenges that occur in the company's external environment. Therefore, environmental adaptability is one of the factors that affect competitive advantage. Competitive advantage is the ability of a company to achieve economic profit above the profit that can be achieved by competitors in the market in the same industry. Marketing performance is also influenced by the company's environment, the success of a company can be seen from how the company faces the pressure of environmental effects in the face of a competitive market. Research was conducted on several batik SMEs in Semarang that created Semarangan Batik. A total of 40 SMEs were used as research samples. Questionnaire instruments were used to collect research data. Path analysis was used to test the influence of these variables. The results showed that environmental adaptability has a positive influence on competitive advantage, market orientation also has a positive influence on marketing performance, competitive advantage also has a positive influence on marketing performance. It is concluded that competitive advantage can mediate the effect of market orientation on marketing performance.